67 Problem solving using the A3 methodology for colposcopy. (13th November 2020) - Vemanamandhi, P; Digumarti, R; Digumarti, L; Odette, S
Abstract : Aim: Cervical cancer screening services are offered to women in two ways-at the centre and in the community. For women screened at the hospital, the reports are reviewed in the clinic and colposcopy is done when needed. The follow up colposcopy coverage was observed to be 95% among the in-house screened women, while in the community it was 12.5%. Our aim is to increase the colposcopy coverage in women with abnormal pap smear in community screening camps from a baseline of 12.5% to 95% over a period of 10 months. Methods: With the help of EQuIPIndia- QIA3 problem solving approach, we have identified the problems leading to low colposcopy follow-up among women screened in the community. The analysis was done using the A3 methodology tools like the Process map, the GEMBA walk, Run chart, Fishbone and Pareto charts. Results: From an average of 12.5%, through the A3 methodology tools we were able to followup 100% of the women who needed colposcopy. Conclusions: A3 methodology is found to be useful for Quality improvement of health care services.